Professional experiences on use of the mental health act in ethnically diverse populations: a photovoice study - Bhui, K; Mooney, R; Joseph, D; McCabe, R; Newbigging, K; McCrone, P; Raghavan, R; Keating, F; Husein, N; The Co-Pact Team (BMJ Publishing Group, 2025)
Background There are long-standing ethnic and racial inequalities in experiences and outcomes of severe mental illness, including compulsory admission and treatment (CAT).